Unjuk Kerja Reaktor Cascade Bentuk Kolom. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Some heterogeneous reactions such as liquid-solid, liquid-liquid were undertaken in the stirred tank batch reactor. To change a batch process into flow process, plug flow reactor is the reactor with the similar performance to the batch reactor. However, it would be faced with problem to attain the plug flow pattern. A cascade of ideally mixed reactor was reactor which has a similar performance with the plug flow reactor especially for heterogeneous system. Experiment was undertaken in the column which was divided into three sections. This is similar with the three mixed flow reactors. Sodium?, chloride was used as a tracer and water as fluid flow. It was investigated two variables such as stirred speed and ratio of impeller diameter to the distance of the cascade. In this paper, Bodenstein number of pipe flow reactor and the number of stages for the cascade were determined experimentally from the residence time distribution of the fluid. It is shown that the results good agreement with the empirical equation proposed by Pawlowski (1962) and Elgeti (1996).